In situ dynamic four-dimensional strong-field ionization tomography - Noam Shlomo; Eugene Frumker (Physical Review Research)
We present an in situ dynamic four-dimensional (4D=3D space + 1D time) laser induced strong field ionization tomography technique, particularly suited for probing far-from-equilibrium systems, such as supersonic and hypersonic pulsed gas jets. By employing a femtosecond laser, temporal resolution is primarily limited by electronic jitter, typically to a few tens of picoseconds. Our proof-of-principle experiment revealed an intriguing phenomenon: a “squeezing” of the gas pulse as it propagates downstream, manifesting as a shortening of the normalized temporal profile of the gas pulse density along the propagation axis, while simultaneously expanding transversely.